Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am given this problem:
let $a\ge0$,$b\ge0$, and the sequences $a_n$ and $b_n$ are defined in this way: $a_0:=a$, $b_0:=b$ and $a_{n+1}:= \sqrt{a_nb_n}$ and $b_{n+1}:=\frac{1}{2}(a_n+b_n)$ for all $n\in\Bbb{N}$

To prove is that both sequences converge and that they have the same limit. I don't know how to show this. I have spent 2 hours on this, no sign of success

share|cite|improve this question
A cute question (+1) – user 1618033 Dec 30 '12 at 9:31
@Chris'ssister, thanks :) – doniyor Dec 30 '12 at 9:33
up vote 23 down vote accepted

The easy way to proceed, is to show that $ b_{n+1} - a_{n+1} = \frac {1}{2} (\sqrt{b_{n}} -\sqrt{ a_{n}})^2$ so $ b_{n} \geq a_{n} \forall n \geq 2$. Then, $a_{n+1} = \sqrt{a_n b_n} \geq a_n$ is an monotonically increasing sequence (after $n=2$). $b_{n+1} = \frac {1}{2} (a_n + b_n) \leq b_n$ is a monotomically decreasing sequnece (after $n=2$). Finally, $$ b_{n+1} - a_{n+1} = \frac {1}{2} (\sqrt{b_{n}} -\sqrt{ a_{n}})^2 \leq \frac {1}{2} (\sqrt{b_n} - \sqrt{a_n} ) ( \sqrt{b_n} + \sqrt{a_n} ) = \frac {1}{2} ( b_n - a_n) \leq \frac {1}{2^n} (b_1-a_1),$$ so the difference between the sequences go to 0. Hence, these sequences converge to the same limit.

Note: Of course we could show that since $a_i \leq b_2$, the limit of $a_i$ exists (since monotonic+bounded). But I think it's more fun to jump directly to the conclusion with the final step.

share|cite|improve this answer
thank you Calvin, – doniyor Dec 30 '12 at 7:27

This is not an answer. Just a long comment which gives a classical formula of Gauss for this common limit.

Let $a$, $b$ be real numbers with $a<b$. We define their arithmetic-geometric mean $M(a,b)$ using the sequences $a_n$, $b_n$ defined as follows: $a_0=a$, $b_0=b$ and inductively

$$ a_{n+1}={ a_n +b_n \over 2}, \qquad b_{n+1}=\sqrt {a_n b_n }\ . $$

The two sequences converge to a unigue common limit $M(a,b)$. Gauss discovered a beautiful formula for $M(a,b)$ which can be expressed as an elliptic integral

$$ { 1 \over M(a,b)} = { 2 \over \pi} \int_0^{ { \pi \over 2}} { d \theta \over \sqrt{ a^2 \cos^2 \theta + b^2 \sin^2 \theta}} \ . $$

share|cite|improve this answer

If $a_n\to l$ and $b_n \to s$ then from $b_{n+1}=\frac{1}{2}(a_n+b_n)$ we get $s=\frac{1}{2}(l+s)\cdots$
To prove that they converge use arithmetic and geometric mean inequality to show (that $a_n\leq b_n$ so ...) they are monotonic ($a_n$ is increasing and $b_n$ decreasing). From $a_n\leq b_n$ conclude they are bounded.

share|cite|improve this answer
Pambos, thanks, now i got it – doniyor Dec 30 '12 at 7:28

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.